Effect of atmospheric pollutants on the corrosion of high power electrical conductors - Part 2. Pure copper - Vera, Rosa (2007)
The research work performed during this study was simultaneously followed with another one published in this journal as Part I. A1 and 6201 A1 alloy. Its aim was to reveal a comparative picture of the joint effect of marine and industrial atmospheric pollutants on the corrosion resistance of wire metals employed for electric transmission conductors. Weight loss after 4, 11, 16 and 24 months exposure was determined and morphology of the attack analysed through SEM-ESEM-EDX. Cu corrosion products showed higher protectiveness than those of Al in marine sites for the lowest [Cl-] and in marine-industrial atmospheres even for the highest SO2 contents. Respect to marine sites where [Cl-] was higher than [SO2] Cu was more susceptible than A1.